Influence of N-acetyl cysteine (NAC) and 2-methylene-1, 3-dioxepane (MDO) on the properties of polymethyl methacrylate (PMMA) bone cement. Issue 21 (16th April 2019) - Zhao, Kangquan; Pi, Bin; Zhao, Liping; Tian, Shoujin; Ge, Jianfei; Yang, Huilin; Sha, Weiping; Wang, Liming
Abstract : The properties of polymethyl methacrylate (PMMA) bone cement make it a popular bone filling material. Abstract : The properties of polymethyl methacrylate (PMMA) bone cement make it a popular bone filling material. However, its disadvantages, such as lack of biodegradability and osteogenesis, restrict its clinical application. Studies have indicated the osteogenic properties of N -acetyl cysteine (NAC) and the biodegradability of 2-methylene-1, 3-dioxepane/methyl methacrylate-based (MDO/MMA) copolymers. In this study, we developed bioactive PMMA cements through modification with fixed concentrations of NAC and different proportions of MDO. The purpose of this study was to compare the mechanical properties, morphology, NAC release, biocompatibility, degradability and mineralization capability of modified bone cements with those of conventional cement. The specific-modified specimens (NAC-p (5% MDO- co -MMA)) exhibited a lower bending modulus but had little effect on compressive strength. This material was morphologically compact and nonporous, similar to conventional PMMA bone cement. NAC could be released from NAC-p (5% MDO- co -MMA) continuously and appropriately. NAC-p (5% MDO- co -MMA) was biologically safe and showed satisfactory tissue compatibility. Ester was introduced into the polymer, which reinforced the degradation properties of NAC-p (5% MDO- co -MMA). NAC-p (5% MDO- co -MMA) enhanced the mineralization capability of osteoblastic cells.